Faktor yang Berhubungan dengan Kepatuhan Pengobatan Diabetes Mellitus - Zaenab M Syahid (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
introduction; without realizing it, diabetes mellitus affects many Indonesians. Destination; know the various factors associated with diabetes mellitus treatment adherence. Methods: Data were obtained from an electronic database using google scholar using the keywords "diabetes mellitus, factors, medication adherence". This literature study was carried out by analyzing scientific articles in Indonesian published from 2015 to 2020, then after selecting journals, 6 qualitative articles were obtained that match the inclusion criteria. Results; found that many factors were associated with adherence to diabetes mellitus treatment, namely age, knowledge, motivation, social (family support and health personnel), education, economy, access, and psychological factors. Health workers and health workers must know the factors associated with diabetes mellitus treatment adherence so that complications can be prevented and handled appropriately. Conclusion; become the basis for health workers and policymakers in planning tips for prevention and control of diabetes mellitus